2024
DOI: 10.1002/aur.3118
|View full text |Cite
|
Sign up to set email alerts
|

Autistic and nonautistic adolescents do not differ in adaptation to gaze direction

Emma K. Ward,
Jan K. Buitelaar,
Sabine Hunnius

Abstract: Predictive processing accounts of autism posit that autistic individuals' perception is less biased by expectations than nonautistic individuals', perhaps through stronger precision‐weighting of prediction errors. Since precision‐weighting is fundamental to all information processing, under this theory, the differences between autistic and nonautistic individuals should be domain‐general and observable in both behavior and brain responses. This study used EEG, behavioral responses, and eye‐tracking co‐registra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The authors suggested that in autism, there is an increased focus on sensory error signals in both exteroceptive and interoceptive domains, which may be inferred as an increased influence of error signals when generating predictions based on sensory input. 28 , 77 However, as previously discussed, predictive models remain untested and debated for the interoception (and also debated for exteroception in autism; see Sapey-Triomphe et al; 78 Cannon et al; 79 Finnemann et al; 80 Ward et al 81 ). Thus, this unified theoretical framework remains empirically untested.…”
Section: Interoceptive Processing and Autismmentioning
confidence: 99%
“…The authors suggested that in autism, there is an increased focus on sensory error signals in both exteroceptive and interoceptive domains, which may be inferred as an increased influence of error signals when generating predictions based on sensory input. 28 , 77 However, as previously discussed, predictive models remain untested and debated for the interoception (and also debated for exteroception in autism; see Sapey-Triomphe et al; 78 Cannon et al; 79 Finnemann et al; 80 Ward et al 81 ). Thus, this unified theoretical framework remains empirically untested.…”
Section: Interoceptive Processing and Autismmentioning
confidence: 99%